Assessing the ability of substrate mapping techniques to guide ventricular tachycardia ablation using computational modelling. (March 2021) - Campos, Fernando O.; Orini, Michele; Arnold, Robert; Whitaker, John; O'Neill, Mark; Razavi, Reza; Plank, Gernot; Hanson, Ben; Porter, Bradley; Rinaldi, Christopher Aldo; Gill, Jaswinder; Lambiase, Pier D.; et al.
A bstract: Background: Identification of targets for ablation of post-infarction ventricular tachycardias (VTs) remains challenging, often requiring arrhythmia induction to delineate the reentrant circuit. This carries a risk for the patient and may not be feasible. Substrate mapping has emerged as a safer strategy to uncover arrhythmogenic regions. However, VT recurrence remains common. Goal: To use computer simulations to assess the ability of different substrate mapping approaches to identify VT exit sites. Methods: A 3D computational model of the porcine post-infarction heart was constructed to simulate VT and paced rhythm. Electroanatomical maps were constructed based on endocardial electrogram features and the reentry vulnerability index (RVI - a metric combining activation (AT) and repolarization timings to identify tissue susceptibility to reentry). Since scar transmurality in our model was not homogeneous, parameters derived from all signals (including dense scar regions) were used in the analysis. Potential ablation targets obtained from each electroanatomical map during pacing were compared to the exit site detected during VT mapping. Results: Simulation data showed that voltage cut-offs applied to bipolar electrograms could delineate the scar, but not the VT circuit. Electrogram fractionation had the highest correlation with scar transmurality. The RVI identified regions closest to VT exit site but was outperformed by AT gradients combined with voltage cut-offs. The performance of all metrics was affected by pacing location. Conclusions: Substrate mapping could provide information about the infarct, but the directional dependency on activation should be considered. Activation-repolarization metrics have utility in safely identifying VT targets, even with non-transmural scars. Graphical abstract: Image 1 Highlights: Safe and accurate detection of targets for catheter ablation remains challenging. Ventricular Tachycardia (VT) was simulated and exit site identified. We assessed the ability of substrate mapping to detect the exit site during pacing. The performance of all metrics was affected by pacing location. Activation-repolarization metrics are useful in identifying ablation targets.